Distribution of Microbial Biomass, Carbon and Nitrogen in a Forest Reserves of Perak, Malaysia - Karam Singh, Daljit Singh; Muharam, Farrah Melissa; Mohamed Zulperi, Dzarifah; Sundara Rajoo, Keeren (UPM Press, 2017)
Microbial biomass is the mass of living microorganisms in a particular ecosystem at a given time . Microbial biomass responds rapidly to different land use management techniques in at different location in forest reserves of Perak, Malaysia